Photoprotection in evergreen Mediterranean plants during sudden periods of intense cold weather - García-Plazaola, J. I.; Olano, J. M. (Trees-Structure and …, 2003)
The photoprotective responses to an abrupt period of exceptional cold weather were studied in several Mediterranean evergreen species with different ecological requirements. The same pattern of response was observed in most of the species with little change in hydrophilic antioxidants (ascorbate and glutathione) and the carotenoid pool, an increase in the content of a -tocopherol, and a night retention of de-epoxidised xanthophylls (antheraxanthin and zeaxanthin). The accumulation of these xanthophylls correlated with a sustained decrease in maximal photochemical efficiency (Fv/Fm). This reduction in the rate of electron transport would reduce the production of superoxide in photosystem I, as well as the subsequent hydrogen peroxide and hydroxyl radical. Thereby if any transitory photooxidative stress is produced under these conditions it should be due mainly to the formation of singlet oxygen by triplet excited chlorophyll within the antenna. Since a-tocopherol is the main scavenger of singlet oxygen and lipid peroxy radicals, the large increase of this antioxidant within the species could be enough to compensate for the higher degree of photooxidative stress, playing an essential role in the survival of vegetation during the incidence of exceptional cold fronts in the Mediterranean region.
Keywords: a-tocopherol; antioxidants; photooxidative stress; xanthophyll cycle